2017
DOI: 10.1038/srep41088
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of flexible CoMoO4@NiMoO4·xH2O and Fe2O3 electrodes for solid-state asymmetric supercapacitors

Abstract: In this work, CoMoO4@NiMoO4·xH2O core-shell heterostructure electrode is directly grown on carbon fabric (CF) via a feasible hydrothermal procedure with CoMoO4 nanowires (NWs) as the core and NiMoO4 nanosheets (NSs) as the shell. This core-shell heterostructure could provide fast ion and electron transfer, a large number of active sites, and good strain accommodation. As a result, the CoMoO4@NiMoO4·xH2O electrode yields high-capacitance performance with a high specific capacitance of 1582 F g−1, good cycling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 62 publications
(62 reference statements)
2
33
1
Order By: Relevance
“…It was also observed that the ESR of our homogeneous structure decreased by at least 68% compared with other heterogeneous structures or different morphologies of NiMoO 4 (Table S1). Moreover, the diameter of the semicircle represents the interfacial charge-transfer resistance (Rct) [51]. In our case, the Rct of Electrodes I, II, and III are 3.0 Ω, 2.35 Ω, and 2.65 Ω, respectively, exemplifying that Electrode II has the best charge-transfer characteristics.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was also observed that the ESR of our homogeneous structure decreased by at least 68% compared with other heterogeneous structures or different morphologies of NiMoO 4 (Table S1). Moreover, the diameter of the semicircle represents the interfacial charge-transfer resistance (Rct) [51]. In our case, the Rct of Electrodes I, II, and III are 3.0 Ω, 2.35 Ω, and 2.65 Ω, respectively, exemplifying that Electrode II has the best charge-transfer characteristics.…”
Section: Resultsmentioning
confidence: 97%
“…Aside from surface area, the impedance of the electrode also has an important effect on the overall behavior of SCs. The impedance properties of the electrodes were investigated in an open-circuit voltage with 5 mV amplitude, utilizing an EIS measurement [15,29,50,51]. Figure 5d displays the Nyquist plots measured in the frequency range of 0.01–100 kHz and the equivalent circuit is shown in the inset.…”
Section: Resultsmentioning
confidence: 99%
“…The energy density of present device is substantially higher than those of recently reported all-solid-state symmetric SCs with electrode materials such as MoS 2 /carbon cloth (5.42 Wh/kg) 43 , GO/PPy (15.1 Wh/kg) 44 , SWCNTs/RuO 2 (18.8 Wh/kg) 36 , rGO-PEDOT/PSS (2.83 Wh/kg) 45 , MWCNTs (3.5 Wh/kg) 46 , N-doped cotton-derived carbon frameworks (NCCF)-rGO (20 Wh/kg) 47 , MoSe 2 (36.2 Wh/kg) 48 , PEDOT:PSS/MWCNT (13.2 Wh/kg) 2 , ZnS/CNTs (22.3 Wh/kg) 37 , ZnCo 2 O 4 /rGO (11.44 Wh/kg) 49 , Pt/n-CNT@PANI (30.22 Wh/kg) 50 , waste paper fibers-RGO–MnO 2 (19.6 Wh/kg) 51 , and porous carbon (7.22 Wh/kg) 52 . Due to current collector-free feature, present ultrathin device showed remarkable energy density, a value considerably higher than even solid-state asymmetric devices, such as CNT/polyaniline//CNT/MnO 2 /GR (24.8 Wh/kg) 53 , carbon aerogel//Co 3 O 4 (17.9 Wh/kg) 38 , graphene(IL-CMG)//RuO 2 –IL-CMG (19.7 Wh/kg) 41 , TiN@GNSs//Fe 2 N@GNSs (15.4 Wh/kg) 54 , NiCo 2 O 4 @PPy//activated carbon (AC) (58.8 Wh/kg) 40 , NiCo 2 O 4 /CC//porous graphene papers (PGP) (60.9 Wh/kg) 55 , γ-MnS//eggplant derived AC (EDAC) (37.6 Wh/kg) 56 , CoS//AC (5.3 Wh/kg) 57 , CoMoO 4 @NiMoO 4 •xH 2 O//Fe 2 O 3 (41.8 Wh/kg) 58 , CuS/3D graphene//3D graphene (5 Wh/kg) 59 , MnO 2 @PANI//3D graphene foam (GF) (37 Wh/kg) 60 , NiCo 2 S 4 /polyaniline//AC (54.06 Wh/kg) 61 , NiCo-LDH//carbon nanorods (59.2 Wh/kg) 39 , Ni(OH) 2 /RGO/Ni//RGO aerogel/Ni (24.5 Wh/kg) 62 , and rGO/CoAl-LDH//rGO (22.6 Wh/kg) 63 .…”
Section: Resultsmentioning
confidence: 99%
“…In the impedance spectra, the starting point intersecting with the X-axis in the high frequency region is series resistance ( R S ) caused mainly by the conductive substrate, connecting wires and contact resistance. The diameter of the semicircle represents the charge transfer resistance ( R CT ) at the electrode/electrolyte interface, curve slope in the low frequency region represents the diffusion-limited processes ( Z w ), respectively [31,[38][39][40][41][42][43][44] . Fig.…”
Section: Electrochemical Performances Of Comoo 4 /Co 1 −X S Electrodementioning
confidence: 99%